2020
DOI: 10.1371/journal.pone.0243882
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of symptoms and quality of life at 35 days after hospitalization for COVID-19 infection

Abstract: Background Characterizing the prevalence and persistence of symptoms associated with COVID-19 infection following hospitalization and their impact is essential to planning post-acute community-based clinical services. This study seeks to identify persistent COVID-19 symptoms in patients 35 days post-hospitalization and their impact on quality of life, health, physical, mental, and psychosocial function. Methods and findings This prospective cohort study used the PROMIS® Instruments to identify symptoms and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
357
3
28

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(419 citation statements)
references
References 22 publications
31
357
3
28
Order By: Relevance
“…The main widespread reported long-term symptoms in COVID-19 patients were chronic fatigue, dyspnea, shortness of breath, chest pains, headache, loss of smell/taste, muscle, and joint pain, followed by depression, anxiety, insomnia, and itchy body, heart palpitations, tachycardia, anorexia, tingling fingertips, and brain fog ( 69 , 70 , 72 , 77 , 84 , 85 , 87 , 91 , 97 , 98 , 101 , 103 , 123 , 138 , 145 147 , 150 , 156 – 159 ). However, it was reported that the number of widespread long-term symptoms were higher for COVID-19 patients who were initially more ill ( 77 , 100 ).…”
Section: Resultsmentioning
confidence: 99%
“…The main widespread reported long-term symptoms in COVID-19 patients were chronic fatigue, dyspnea, shortness of breath, chest pains, headache, loss of smell/taste, muscle, and joint pain, followed by depression, anxiety, insomnia, and itchy body, heart palpitations, tachycardia, anorexia, tingling fingertips, and brain fog ( 69 , 70 , 72 , 77 , 84 , 85 , 87 , 91 , 97 , 98 , 101 , 103 , 123 , 138 , 145 147 , 150 , 156 – 159 ). However, it was reported that the number of widespread long-term symptoms were higher for COVID-19 patients who were initially more ill ( 77 , 100 ).…”
Section: Resultsmentioning
confidence: 99%
“…Observational studies deriving from different populations (USA, Europe and Asia) revealed a variable proportion of persistent symptoms following SARS-CoV-2 infection (Table 1, Appendix Table 2). Early studies provided evidence of persistent COVID sequelae reporting short term outcomes covering the post-acute phase (4-12 weeks) of COVID-19 [8,13,17,[19][20][21][22][23]27]. Most recent publications present data from larger cohorts with longer follow-up periods (beyond 12 weeks) illustrating the multisystemic manifestations of the so called "long" or "chronic'' COVID [10,12,18].…”
Section: Epidemiologymentioning
confidence: 99%
“…Recently published cohort studies have reported symptoms from most body systems in following the acute disease phase reflecting its multi-systemic nature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Table1, Appendix Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of post-viral syndromes has been reported to involve a complex interplay between the viral loads and the humoral and cellular immune responses that could elicit both direct non-immunological and indirect immune effects [ 3 , 5 ]. However, the available knowledge of post-COVID-19 syndrome is still poor and controversial due to the lack of a consensus definition [ 6 ], the heterogeneity of the investigated population and diagnostic follow-ups [ 1 , 2 , 7 , 8 ]. A better understanding of the post-COVID-19 syndrome and the dynamics and the nature of immune response to SARS-CoV-2 infection might assist in identifying long-haulers and appropriate pathways of care.…”
Section: Introductionmentioning
confidence: 99%